Pengaruh Kreativitas Dosen Terhadap Prestasi Belajar Mahasiswa Pada Matakuliah Ekonomi Mikro Di Program Studi Perbankan Syariah Jurusan Syariah dan Ekonomi Islam STAIN Watampone - zulkifli zulkifli (Institut Agama Islam Negeri (IAIN) Bone, 2017)
The purpose of this study is to find out how the influence of the creativity of lecturers in the learning process on student learning achievement in the Microeconomics Course in the Islamic Banking Study Program of the Sharia and Islamic Economics Department of STAIN Watampone. Data collection techniques used were questionnaires and documentation. The data analysis technique used is a simple linear regression with the help of SPSS 20.00 software for Windows. Based on the results of the study show that the creativity of lecturers in the learning process has a positive and significant effect on student learning achievement in the Microeconomics Course in the Islamic Banking Study Program of the Shariah and Islamic Economics Department of STAIN Watampone